Corncob Prepared Bonded Dust Suppression Materials with the Performance Analysis - Matsumnra, Phisit; Khalafi, Bahman (Journal of Green Energy and Environmental Engineering, 2026)
To mitigate coal dust contamination jeopardizing railway operational safety attributed to suboptimal efficacy of conventional dust suppression agents, this investigation formulated an eco-friendly bio-derived adhesive particulate suppressant. Using corncob agricultural waste as the primary substrate, combined with acrylic acid monomer, ethylene glycol dimethacrylate as the crosslinker, and sodium dodecyl sulfate as the surfactant, a corncob-based dust suppression material was prepared. Comprehensive mechanistic investigation of tetracycline sorption onto porous biochar derived from peanut shells (PFBC) revealed multiple uptake pathways encompassing pore filling, π–π stacking interactions, hydrogen bonding, and metal complexation. Post-modification characterization indicated substantial enhancement of porosity, and surface oxygen-containing functional groups, with nanometer-scale particle dimensions. Sorption isotherm analysis confirmed Langmuir behavior with pseudo-second-order kinetic modeling, indicating monolayer chemisorption as the rate-limiting mechanism, achieving maximum sorption capacity of 500.0 mg/g at 25°C. The particulate suppression agent exhibited cohesive structural properties, forming a compact, flaky solidified stratum at the coal dust interface, thereby effectively sealing interstitial voids among particulate matter. The particulate suppression agent exhibited cohesive structural properties, forming a compact, flaky solidified stratum at the coal dust interface, thereby effectively sealing interstitial voids among particulate matter. Dynamic wetting characteristics of material molecules at the coal-water interface were revealed, comprising rapid molecular diffusion in early stages, oriented aggregation followed by cross-linked network development during intermediate phases, and final equilibration attained at 300 picoseconds. The unique bifunctional molecular configuration of the agent markedly augmented microscopic interfacial interactions between coal and aqueous molecules. Under these specified conditions, particulate peak Concentration reached 3.0 mg/m³ with asymptotic stabilization at 1.0 mg/m³. Comprehensive mechanistic investigation of tetracycline sorption onto porous biochar derived from peanut shells (PFBC) revealed multiple uptake pathways encompassing pore filling, π–π stacking interactions, hydrogen bonding, and metal complexation. Post-modification characterization indicated substantial enhancement of specific surface area, pore volume, and surface oxygen-containing functional groups, with nanometer-scale particle dimensions. Sorption isotherm analysis confirmed Langmuir behavior with pseudo-second-order kinetic modeling, indicating monolayer chemisorption as the rate-limiting mechanism, achieving maximum sorption capacity of 500.0 mg/g at 25°C. The unique dual-affinity molecular configuration of the agent markedly augmented microscopic interfacial interactions between coal and aqueous molecules. Experimental investigations utilizing a simulation experimental system established the optimal application concentration at 1.5% mass fraction. Under these specified conditions, particulate peak concentration reached 3.0 mg/m³ with asymptotic stabilization at 1.0 mg/m³. The temporal duration of particulate generation resulting from aerodynamic perturbation was 46 seconds, yielding optimal comprehensive dust suppression efficacy.